Eksperimen Strategi Pembelajaran Think Pair Share (Tps) Dan Problem Based Learning (Pbl) Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Belajar Siswa Kelas VIII Semester Genap Mtsn Gondangrejo Tahun 2015/2016 - Sartikawati, Nike; Rita P. Khotimah, S.Si., M.Sc (2016)
ABSTRACT Nike Sartikawati/ A410120057. EKSPERIMEN STRATEGI PEMBELAJARAN THINK PAIR SHARE (TPS) DAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI MOTIVASI BELAJAR SISWA KELAS VIII SEMESTER GENAP MTSN GONDANGREJO TAHUN 2015/2016. Skripsi. Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. Maret, 2016. Mathematics learning outcomes is very important but there are still students' mathematics learning outcome are less satisfactory. Unsatisfactory learning outcome can be influenced by several factors including the factor of motivation and learning strategies used by teachers in presenting the teaching materials. The aim of research to describe and analyze: (1) the effect of learning strategies Think Pair Share (TPS) and Problem Based Learning (PBL) on the results of learning matematics, (2) the influence student motivation for learning outcame matematics,(3) the interaction between learning strategy and students' motivation to learn math results. The type of the research is experiment with quasi experimental design. The study population was all eighth grade students MTsN Gondangrejo second semester of 2015/2016. The study sample consisted of two classes. The test method uses data collection and documentation. Data were analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there was an effect of learning strategies Think Pair Share (TPS) and Problem Based Learning (PBL) on the results of studying mathematicst, with FA=43.05281 (2) there is influence student motivation for learning outcomes mathematics, FB = 38.73786 (3) there is no interaction between the learning strategies and students' motivation to learn math results, with FAB = 0.856143. Keyword: TPS, PBL, mathematics learning outcomes and student motivation.